Hubungan Kausal Dukungan Sosial Orang Tua dan Pemilihan Program Studi oleh Mahasiswa PGMI di Perguruan Tinggi Keagamaan Islam - Ramadhani, Nadira Novia; Khaeroni, Khaeroni; Meiliawati , Fithri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The decision-making process in choosing a study program is a crucial stage that is influenced by various factors, especially social support from parents. This study examines the influence of parental social support on the decision-making of first-year students in choosing the Elementary Madrasah Teacher Education Study Program at Islamic higher education institution in Indonesia. Using a quantitative approach and survey method, data were collected through a structured questionnaire. The research sample consisted of 60 first-year students from two Islamic religious colleges. Data analysis was carried out using simple linear regression and showed a significant influence of parental social support on student decision-making, as indicated by the R-squared value of 0.494. These results indicate that 49.4% of the variability in the decision-making process can be explained by parental social support. This finding confirms the importance of the role of parental social support in helping students make the right and responsible educational choices.